Designing low-weight switched reluctance motors for electric multirotor propulsion system - Biczyski, Marcin; Sehab, Rabia; Krebs, Guillaume; Whidborne, James F.; Luk, Patrick Chi-Kwong (Society of Electricity, Electronics and Information and Communication Technologies, 2021)
One of the ways in which we can facilitate the introduction of UAVs, especially autonomous ones, into public airspaces is to increase their safety. Brushless DC motors used for the majority of RC vehicles have multiple vulnerabilities, most of which connected with the reliance on neodymium magnets. To reduce the number of possible points of failure, switched reluctance motor technology is researched as an alternative, because of reliability, robustness and the lack of rare earth materials. To take advantage of these features, a motor design optimization process was adopted, which uses 2D FEM models. These do not capture certain 3D effects, such as end-winding inductance, what has led to considerable decrease in performance when used in a multirotor propulsion chain. The presented approach keeps the 2D-based optimization approach and focuses on improving the performance as a next step in the design process. Four methods are evaluated – two of them aiming at improving the motor’s flux network and two focused on increasing the voltage. Taking into consideration the application, the methods are assessed not only based on performance improvement, but also on predicted platform weight change and price increase.
Conference Poster Session: P2-20